Assessment of lipoedema awareness among polish women- online survey study - Rita Hansdorfer-Korzon; Monika Czerwińska; Jacek Teodorczyk; Jolanta Szamotulska (BMC, 2023)
Abstract Background Lipoedema is an adipose tissue disorder that is still not fully understood. The primary purpose of this study is to explore the state of knowledge and understanding of lipoedema among Polish women. The secondary aim is to investigate the possible association between knowledge and factors such as BMI, self-reported symptoms, and age. Methods One hundred seventy polish women took part in an online survey study that was posted to social media groups and forums in January 2022. The survey consisted of 12 questions and aimed at assessing the basic knowledge about lipoedema. Results The least proportion of participants (4%) could correctly indicate the methods of lipoedema treatment. The accurate definition of lipoedema was indicated only by 7% of women, 12% identified characteristic features of lipoedema, and 37% correctly evaluated lipoedema curability. The greatest proportion of respondents knew the differences between obesity and lipoedema (50%). Conclusions Awareness of lipoedema among women is deficient. A significant proportion of the respondents report the occurrence of lipoedema symptoms. In order to improve the situation of lipoedema patients, it is crucial to increase the knowledge about this condition both among medical professionals and the general public.